Felipe González de Castejón y Tovar (1745-1803): founder member and first director of the Real Sociedad Tudelana de los Deseosos del Bien Público - Guijarro Salvador, Pablo (Huarte de San Juan. Geografía e Historia, 2011)
The “Real Sociedad Tudelana de los Deseosos del Bien Público” was the only “Sociedad de Amigos del País” founded in Navarra in the XVIIIth century, what it makes one of the most important enlightened phenomenon in the old kingdom. Its first director, Felipe González de Castejón y Tovar, belongs to a military saga, in which stands out his uncle, Pedro González de Castejón y Salazar, minister of Navy, whose mandate coincides with the Society foundation in 1778. This essay aspires to define the profile of a man that, together with the marquises of San Adrian, was one of the most relevant members of the Society. Through a study of his social origins, education, marriage, economic status, etc. tries to understand his connection with the Enlightenment mentality.